Effect of Transcranial Direct Current Stimulation (TDCS) on Depression in Older Adults: A Pilot Randomized Controlled Trial - M. Zareie; S. Balal Habashi; P. Farokhnezhad Afshar (Клиническая и специальная психология)
Depression is one of the most common disorders in older adults. Depression management is one of the problems of geriatrics. This study evaluated the effect of Transcranial Direct Current Stimulation (TDCS) on depression in older adults. This study is an unblinded randomized controlled trial. We selected 60 patients with depression based on the Geriatric Depression Scale (GDS) and randomly divided them into two groups. The intervention group received Sertraline 25–50 mg and TDCS for five days (each day: 20 min at two mA). The control group received Sertraline (25–50 mg). Data were analyzed using SPSS v. 22 software. The mean age was 72 years. There was a significant decrease in GDS score before and after the study in the control group (8.6±1.55 to 6.40±1.45, p=0.001) and the intervention group (8.86±1.35 to 5.46±0.91, p=0.001). The comparison of the two groups shows a significant difference in the changes in the GDS score (p=0.01). The results of this study suggest that Transcranial Direct Current Stimulation (TDCS) with medication affects depression in old patients, but more studies are needed.